The embedded librarianship in scholarship and research among academic librarians in the Malaysian research universities / Khasiah Zakaria - Zakaria, Khasiah (Institute of Graduate Studies, UiTM, 2016)
This study investigates the concept of the embedded librarianship in relation to scholarship and research support. This study started with the aim of investigating the perception of academic librarianship in scholarship, research and knowledge production. However an embedded librarianship in support of scholarship and research emerged. Embedded librarianship in this study refers to a situation where librarians embedded programme in training users, provide ready reference, perform in-depth topical research, and involve in library resource development. The population of the study comprises the academic librarians from five Malaysian researcher universities. This quantitative method of study used questionnaire as the instrument to collect data. Eighty nine items from three variables formed the basis of a survey instrument using a seven-point interval scale. The instrument was distributed to the two hundred twenty academic librarians working in the five Malaysian research universities. A total of one hundred and thirty nine (59%) respondents returned the questionnaire. A combination of descriptive statistics, means ranking, one-way analysis of variance (ANOVA), independent-samples t test, regression and Pearson’s Product Moment Correlations were used in this study using the SPSS version 19.0. The findings revealed that the level of scholarship roles among academic librarians is quite high, particularly in the teaching of information literacy such as accessing and using information. Academic librarians are involved in research support activities but only at a moderate level…